Seafood Discards: A Potent Source of Enzymes and Biomacromolecules With Nutritional and Nutraceutical Significance - Nag, Moupriya; Lahiri, Dibyajit; Dey, Ankita; Sarkar, Tanmay; Pati, Siddhartha; Joshi, Sanket; Bunawan, Hamidun; Mohammed, Arifullah; Edinur, Hisham Atan; Ghosh, Sreejita; Ray, Rina Rani (Frontiers in Nutrition, 2022)
At recent times the seafood industry is found to produce large volumes of waste products comprising shrimp shells, fish bones, fins, skins, intestine, carcasses, along with voluminous quantity of waste-water as effluents. These sea food industry effluents contain large quantities of lipids, amino acids, proteins, polyunsaturated fatty acids, minerals and carotenoids mixed with the garbage.Thisdebris not only causes a huge wastage of various nutrients but also roots severe environmental contamination.Hence, the problem of such sea food industry run offs needs to be immediately managed with a commercial outlook. Microbiological treatment may lead to the valorization of seafood wastes, the trove of several useful compounds into value-added materials like enzymes namely lipase, protease, chitinase, hyaluronidase, phosphatase etc. and organic compounds like bioactive peptides, collagen, gelatin, chitosan, mineral- based nutraceuticals. Such bioconversion in combination with a bio-refinery strategy possesses the potential for environment- friendly and inexpensive management of discards generated from seafood, which can sustainably maintain production of seafood. The compounds that are being produced may act as nutritional source or as nutraceuticals, the foods with medicinal value. Determined utilization of seafood discard not only reduces the obnoxious deposition of waste but add economy in the production of food with nutritional and medicinal importance and thereby meet up the long-lasting global demand of making nutrients and nutraceuticals available at a nominal cost.